Answer:
Step-by-step explanation:
Since angle ABD is 133 degrees and the sum of the angles in a triangle is 180 degrees, it means that
m∠ DAB + 133 + 22 = 180
m∠ DAB = 180 - 155 = 25 degrees
Also, ∆ ADC is an isosceles triangle because two of its sides are equal. It also means that the base angles are equal. Thus,
m∠ A = m∠ B
Therefore,
m∠ A + m∠ B + angle D = 180
m∠ A + m∠ B = 180 - 22 × 2
m∠ A + m∠ B = 180 - 44 = 136
m∠ A = m∠ B = 136/2 = 68 degrees
m∠ CAB + m∠ DAB = m∠ A
Therefore,
m∠ CAB = 68 - 25 = 43 degrees
Since ∆ ABC is isosceles, then
m∠ CAB = m∠ ACB
m∠ ACB = 43 degrees
m∠ ABC = 180 - (43 × 2) = 180 - 86
m∠ ABC = 94 degrees
m∠ BCD = 68 - m∠ ACB
m∠ BCD = 68 - 43 = 25 degrees
She spent $7.44 because 3.28 + 1.27 + 0.56 + 2.33 = 7.44
Answer:
x=0.2
Step-by-step explanation:
<span>-5p^5q^4/ 8p^2q^2
= -5p^3q^2
</span><span>exponent on the p will be 3
answer
</span><span>C.3</span>
Answer:
What question? We need more context